Why Study the History of Neuroscience? - Brown, Richard E. (Frontiers in Behavioral Neuroscience, 2019)
History is the memory of a discipline and the memory of the past depends on the study of the present traces of the past; the things left behind: artifacts, equipment, written documents, data books, photographs, memoirs, etc. History is an integral part of neuroscience. Each time we talk about the brain, do an experiment, or write a research paper, we are involved in history. Each published experiment is a historical document; it relies on past research (the introduction), procedures developed in the past (methods) and as soon as new data are published, they become history, and become embedded into the history of the discipline (discussion). In order to be transparent and to be replicated, each experiment requires its own historical archive. Studying history means researching books, documents and objects in libraries, archives, and museum; looking at data books, letters and memos, talking to scientists, and reading biographies and autobiographies. History can be made relevant by integrating historical documents into classes and by using historical websites. Finally, doing historical research can be interesting, entertaining, and lead to travel to exotic places and meeting interesting people.